Graphene based integrated tandem supercapacitors fabricated directly on separators. (July 2015) - Chen, Wei; Xia, Chuan; Alshareef, H.N.
Abstract: Integrated supercapacitors with extended operation voltage are important for high energy density storage devices. In this work, we develop a novel direct electrode deposition on separator (DEDS) process to fabricate graphene based integrated tandem supercapacitors for the first time. The DEDS process generates compact graphene‐polyaniline electrodes directly on the separators to form integrated supercapacitors. The integrated graphene‐polyaniline tandem supercapacitors demonstrate ultrahigh volumetric energy density of 52.5 W h L −1 at power density of 6037 W L −1 and excellent gravimetric energy density of 26.1 W h kg −1 at power density of 3002 W kg −1 with outstanding electrochemical stability for over 10, 000 cycles. This study show great promises for the future development of integrated energy storage devices. Graphical abstract: Graphene based integrated tandem supercapacitors are fabricated using direct electrode deposition on a separator (DEDS) process and demonstrated for the first time. The integrated graphene‐polyaniline tandem supercapacitors show ultrahigh volumetric energy density of 52.5 W h L −1 at power density of 6037 W L −1 and excellent gravimetric energy density of 26.1 W h kg −1 at power density of 3002 W kg −1 with outstanding stability for more than 10000 cycles. Highlights: A novel direct electrode deposition on separator (DEDS) process is developed to fabricate graphene based integrated tandem supercapacitors for the first time. The integrated graphene‐polyaniline tandem supercapacitors show both very high volumetric and specific capacitances. Ultrahigh volumetric energy and power densities can be achieved with outstanding long term cycling stability. The strategy show great promises for the future development of integrated energy storage devices.